Epigenetic Risk Factors in PTSD and Depression - Raabe, Florian J.; Spengler, Dietmar (Frontiers in Psychiatry, 2013)
Epidemiological and clinical studies have shown that children exposed to adverse experiences are at increased risk for the development of depression, anxiety disorders and PTSD. A history of child abuse and maltreatment increases the likelihood of being subsequently exposed to traumatic events or of developing PTSD as an adult. The brain is highly plastic during early life and encodes acquired information into lasting memories that normally subserve adaptation. Translational studies in rodents showed that enduring sensitization of neuronal and neuroendocrine circuits in response to early life adversity are likely risk factors of life time vulnerability to stress. Hereby, the hypothalamic-pituitary-adrenal (HPA) axis integrates cognitive, behavioural and emotional responses to early-life stress and can be epigenetically programmed during sensitive windows of development. Epigenetic mechanisms, comprising reciprocal regulation of chromatin structure and DNA methylation, are important to establish and maintain sustained, yet potentially reversible, changes in gene transcription. The relevance of these findings for the development of PTSD requires further studies in humans where experience-dependent epigenetic programming can additionally depend on genetic variation in the underlying substrates which may protect from or advance disease development. Overall, identification of early-life stress associated epigenetic risk markers informing on previous stress history can help to advance early diagnosis, personalized prevention and timely therapeutic interventions, thus reducing long-term social and health costs.